Development and assessment of a solar-driven charging station integrated with liquid CO2 as an energy storage option - Erdemir, Dogan; Dincer, Ibrahim (ELSEVIER, 2023)
It is expected that there will soon be a substantial increase in the number of charging stations developed and built in the near future due to a drastic increase in the number of electric vehicles. Charging stations pose a major concern for the grid because of the additional load they will generate. The development of self-sufficient and renewable-powered charging stations is therefore essential. This study develops a novel solar-powered charging station that integrates liquid CO2 as an energy storage option for dedicated off-grid conditions. Solar energy is captured and stored by converting gaseous CO2 into liquid to operate the system without requiring grid power. The stored liquid CO2 is then expanded via turbine for power generation when solar power is unavailable or insufficient to meet demand. We investigate the effects of utilizing yearly dynamic solar data and yearly average solar data on estimating off-grid conditions and system performance. Based on the results, it appears that using yearly averages can lead to an error of 37 % in estimating the solar PV area to be allocated for off-grid conditions. The total area of PV panels is found to be 100,723 m2, and it results in 63,938 m2 for the cases when yearly dynamic and yearly average solar data are used. The overall energy and exergy efficiencies of the developed systems are further calculated to be 0.062 and 0.066, respectively.
Keywords: Charging station; Energy storage; Liquid carbon dioxide; Energy management; Electric vehicle; Exergy; Efficiency; CARBON-DIOXIDE; PERFORMANCE ANALYSIS; SYSTEM; Energy & Fuels